Surveillance and datafication in higher education: Documentation of the human - Gourlay, Lesley (Proceedings of the International Conference on Networked Learning, 2024)
It has become a commonplace in educational research and policy discourses to state that digital technology has ‘transformed’ the nature of higher education, and even the university itself, leading to what is claimed to be more interactive or less hierarchical formats and engagement, in which traditional modes of teaching such as the lecture, are claimed to be obsolete. These narratives, arguably, express a widespread desire for ‘transformation’ in the university. In terms of digital education, this has been expressed variously in the apparently benign ideologies of ‘active learning’, ‘connectivism’, and ‘the flipped classroom’, all of which share common values, those which prize student interaction, and observable engagement, both online and in the face-to-face setting. Although these constructs appear to be ‘student centred’ and progressive, critics (e.g. Macfarlane 2017) have pointed out that an emphasis on student performance of a particular form of engagement and identity in higher education may in fact threaten the fundamental values of academic freedom. In parallel, regimes of audit concerning academic performance have become more prevalent in higher education, with metrics measuring publications and impact becoming more influential on academic careers. I have argued elsewhere (Author 2020) that this tendency is greater in the context of digital education, where performativity, surveillance and regulation are intensified via digital technologies, as part of a broader ‘culture of surveillance’ in society (Lyon 2018). As recent commentators have argued (e.g. Williamson 2017a), the increased use of big data to track and monitor student activity, has the effect of ‘datafying’ them as human subjects; the same could be said for the technology of the h-index for academics. In this paper I will combine insights of digital education research, science and technology studies and information science in order to interrogate the nature and effects of this increased ‘datafication’ of higher education, looking at two examples; learner analytics and the author publication metric h-index. I will argue that these two digitally-mediated ‘documenting’ practices share several features; they have a supervisory or surveilling function, they are underpinned by particular ideologies, and they carry normative force regarding the nature of ‘desirable’ subjectivities and practices. I conclude that there is a need to sustain a critical agenda of research around these technologies of surveillance and documentation, particularly in the current context in which ‘discourses of inevitability’ surrounding digitisation of higher education prevail.